Spesies Tumbuhan Invasif di Hutan Musim Taman Nasional Baluran, Situbondo, Jawa Timur - Hatipah Salamah; Evi Muliyah; Siti Dela Oktavia; Savira Nuraini; Feby Amelia Anandai; Riska Luthfiah (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Indonesia is rich in biodiversity, with 1.75% of all plants identified worldwide. The biggest threat to biodiversity is invasive plant species. Baluran National Park is a conservation area in Indonesia with various ecosystems and every year; the area experiences increased growth. However, research on invasive plants in one of the Baluran National Park areas, namely the Monsoon Forest, has not been identified. This research aims to identify invasive alien plants and their impacts, which are supported by environmental factors in the Monsoon Forest of Baluran National Park. The method used was direct exploratory research by creating 3 sample plots measuring 10x10 m. The data analysis technique was carried out using quantitative analysis. The research results show that the Monsoon Forest of Baluran National Park has biodiversity in the medium category (H'= 2.808%). Thirty-three species of invasive plants were found, with 1431 individuals. The highest Importance Value Index (IVI) for invasive foreign plants is Digitaria sanguinalis (L.) Scop. 25.4%, Desmanthus virgatus (L.) Willd. and Oplismenus hirtellus (L.) 14.43%, Barleria prionitis L. 12.73%. and the Bidens subalternans, 11.33%.